2016
DOI: 10.21511/imfi.13(2-2).2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Various moving average convergence divergence trading strategies: a comparison

Abstract: Some studies published recently (Dejan Eric, 2009;R. Rosillo, 2013; Terence Tai-Leung Chong, 2008;Ülkü and Prodan, 2013) uncover that moving average convergence divergence (MACD) trading rules have predictive ability in many countries. The MACD trading strategies applied by these papers to execute the trading signals are various. This study analyzes the performance of a MACD trading strategy (MACD-4 in the current study), which is applied popularly by practitioners, but was not tested by prior academicians. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…MACD bersifat informatif karena memberikan dasar untuk pengambilan keputusan yang dapat mengarah pada investasi nilai dalam perdagangan ekuitas. Hung (2016) menyimpulkan bahwa strategi MACD memiliki kemampuan prediksi yang lebih efektif jika digunakan dalam lingkungan pasar modal yang memiliki cost tinggi.…”
Section: Abstrakunclassified
“…MACD bersifat informatif karena memberikan dasar untuk pengambilan keputusan yang dapat mengarah pada investasi nilai dalam perdagangan ekuitas. Hung (2016) menyimpulkan bahwa strategi MACD memiliki kemampuan prediksi yang lebih efektif jika digunakan dalam lingkungan pasar modal yang memiliki cost tinggi.…”
Section: Abstrakunclassified
“…(6) The best practice of enablers: From the study results, it was found that the best classifier is the decision tree C4.5 algorithm for the TEJ dataset, and the best model is Models D and E in terms of average accuracy. (7) Interpretation of two data-split methods: It was found that the cross-validation data approach makes more appropriate use of the TEJ dataset than the percentage-split data approach.…”
Section: Helpful Research Findings and Management Implicationsmentioning
confidence: 99%
“…MA has an average of closing prices of a specific number of time periods, such as a 7-period MA for seven days, which defines a flowing correlation between the time period and the money rate [5]. MACD uses exponential moving averages (EMAs) to calculate its value, equal to the value of the shorter time of EMAs and less than the value of the longer time of EMAs [7]. Furthermore, many varied and diverse perspectives for MA and MACD were studied for these purposes, such as EMA, simple moving average (SMA), or weighted moving average (WMA), and variety of MACD-1-4 [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capital gain relates to the return investors receive; the higher the capital gain value, the greater the stock return obtained (Kususma & Topowijono, 2020). To measure stocks, namely the relative strength index indicator (Alhilfi, 2019), moving average convergence divergence (Hung, 2016), Bollinger bands (Day et al, 2023), and stochastic oscillator.…”
Section: Introductionmentioning
confidence: 99%